Nuclear energy :a new threat to South Africa's Heritage? The case of public participation and heritage protection at thyspunt, Eastern Cape, South Africa - Hlangani, Mfundo (My University, 2019)
This study focuses on Thyspunt area in the Eastern Cape Province where an extensive Environmental Impact Assessment (EIA) was conducted for over 5 years. The Heritage Impact Assessment (HIA) revealed that Thyspunt contains extensive heritage resources that will be destroyed as result of a Nuclear Power Station (NPS) development. Therefore this study investigates the role played by Interested and Affected Parties (I&APs) during the EIA Public Participation Process (PPP) as a tool for heritage protection. A thematic analysis of the comments submitted by I&APs during the various stages of the EIA reveal five central themes that center around the importance of heritage to the I&APs’ concerns with nuclear safety, lack of access to information, the participant’s mistrust in the EIA process and technical procedure, and recommendations for the use of cleaner and renewable energy. The study reveals the effectiveness of the EIA public participation process as a vehicle for resistance and tool for local communities to participate in a decision-making process and heritage management in South Africa. Also, it reveals how heritage can give a voice to groups and communities. Although heritage may have multiple or different meanings and communities may have differing agendas, the PPP contributed in halting the development at Thyspunt.
A minor dissertation submitted in partial fulfilment of the degree of Master of Science Archaeological Heritage Management in the Faculty of Science division of Archaeology School of Geography, Archaeology and Environmental Studies, 2019
Keywords: Nuclear energy; Nuclear power plants